Rapidly solidified alloys processes, structures, properties applications - Liebermann, Howard H (Materials engineering (Marcel Dekker, Inc.), 1993)
This volume details the principles underlying rapid solidification processing, material structure and properties, and their applications. This practical resource presents a manifold approach to both amorphous and crystalline rapidly solidified metallic alloys.;Written by over 30 internationally acclaimed specialists in their respective fields, Rapidly Solidified Alloys: surveys nucleation and growth studies in undercooled melts; examines various processes for the production of rapidly solidified alloys; discusses the compaction of amorphous alloys; describes surface remelting treatments for the rapid solidification of surface layers and the resultant improved workpiece properties; covers the closely related topics of structural relaxation, atomic transport and other thermally induced processes; demonstrates microstructure-property relationships in rapidly quenched crystalline alloy systems and their beneficial effects in applications; and elucidates the basic, engineeering, and applications-oriented magnetic properties of amorphous alloys.;Furnishing more than 2300 literature citations for further study of specific subjects, Rapidly Solidified Alloys is intended for materials, mechanical, product, and civil engineers; metallurgists; magneticians; physicists; physical chemists; and graduate students in these disciplines.